Resolving cryptic diversity in the Chromis viridis species complex (Pomacentridae): a multilocus phylogenetic and morphometric reassessment of species boundaries - M. U. Rekha; Teena Jayakumar T. K.; Abhilash C. P.; Ahamed Rasheeq A.; Saikrishnan K. R.; Vallarasu R.; Gladston Y.; Kajal Chakraborty; Ajithkumar T. T. (Frontiers in Marine Science, 2026)
The blue-green damselfish, Chromis viridis (Cuvier, 1830), is widely distributed across Indo-Pacific coral reefs and is among the most heavily traded marine ornamental fishes. Recent molecular studies have suggested the presence of cryptic diversity within the C. viridis complex, but species boundaries remain unresolved. Multilocus phylogenetic analyses incorporating three mitochondrial markers—cytochrome c oxidase subunit I (COI), cytochrome b (cytb), and the mitochondrial control region (D-loop)—and two nuclear markers, recombination-activating gene 1 (RAG1) and recombination-activating gene 2 (RAG2), were performed to assess lineage diversification within the Chromis viridis species complex. Specimens collected from the Lakshadweep Archipelago and the Gulf of Mannar, India, formed a distinct and well-supported lineage that was clearly separated from C. viridis sensu stricto and other congeners in phylogenetic reconstructions and genetic distance analyses. Multiple species-delimitation approaches consistently supported the recognition of this lineage as an independently evolving taxon, and morphometric analyses revealed corresponding differences in body proportions and meristic characters. Based on the concordance of molecular and morphological evidence, a new species, Chromis veneta sp. nov., is herein described from the Indian Ocean. The new species differs from C. viridis in having a relatively elongate body, narrower caudal peduncle, distinctive body pigmentation, yellowish to orangish distal fin margins, and a deeply forked caudal fin with elongate lobe tips. Additional diagnostic features include differences in dentition, gill-raker counts and sagittal otolith morphology. The discovery of C. veneta sp. nov. highlights underestimated diversity within the C. viridis complex and underscores the importance of integrative taxonomy in revealing cryptic reef-fish diversity.

Assessment of district-level climate vulnerability in Kerala using an integrated IPCC framework - K R Riya; B. Ajithkumar; P. Lincy Davis; Arjun Vysakh; R Sarath (Journal of Earth System Science, 2026)

CRISPR/Cas9-Mediated Genome Editing for Abiotic Stress Tolerance in Crops: Current Advances and Future Prospects - Ajithkumar V.; Soni K. B.; Swapna Alex; Anuradha T.; Rehna Augustine; Manju R. V. (Plant Molecular Biology Reporter, 2025)

Synthesis, Fluorescence Properties and Comparison Studies on 2-aminophenol Derivatives: Insights from DFT, Topology, Non-covalent Interactions and Molecular Docking Studies - Natarajan Elangovan; R. Yogeswaran; G. Ajithkumar; S. K. Elagan; Samy F. Mahmoud (Journal of Fluorescence, 2025)

Socio-economic status of commercial seaweed growers of Tamil Nadu, India after COVID-19 - V. Veeragurunathan; K. Sundaragnanam; P. Gwen Grace; S. GopalaKrishnan; V. Ajithkumar; S. Dinesh Kumar; Ramalingam Dineshkumar; Vaibhav A. Mantri (Journal of Applied Phycology, 2025)

Evaluation of Lactiplantibacillus argentoratensis MYSJK8 from Jackfruit for Its Multifarious Antibacterial, Probiotic, Plant Growth Promoting and Bio-control Attributes - Pruthviraj; M. K. Naik; Suresha D. Ekabote; M. S. Nandish; K. Ajithkumar; B. Shruthi; G. Adithi; S. Divyashree; M. Y. Sreenivasa (Journal of Crop Health, 2024)

Mapping of endemic and risk free areas for mycotoxigenic fungi and detection of aflatoxin and fumonisin in major maize growing regions of Karnataka, India - K. Ajithkumar; M. K. Naik; A. S. Savitha; S. Mahadevakumar; M. Y. Sreenivasa; N. L. Rajesh (Indian Phytopathology, 2024)

Acute Respiratory Syndrome Mimicking Shipping Sickness in Theileria buffeli Infected Buffalo Calf - Varghese Raina; Y. Ajith; Sasi Adithya; S. Anandu; N. Athira; K. S. Athira; P. Preena; K. Vinodkumar; K. Mathew Manju; C. S. Mahima; Jose Akshaya; B. Bruce Alby; et al. (Acta Parasitologica, 2024)

Phytopathological investigations of collar rot of chia (Salvia hispanica L.) caused by Macrophomina phaseolina – A new host record from India - Josna Joy; S. Mahadevakumar; K. Ajithkumar; A.S. Savitha; K.R. Sridhar; S. Chandranayaka; N. Lakshmidevi (Physiological and Molecular Plant Pathology, 2024)

Biometeorological analysis on the molecular incidence of babesiosis and ehrlichiosis in dogs - Y. Ajith; Sasi Adithya; Varuna P. Panicker; N. Athira; V. Beena; M. Saifudeen Safeer; P. Preena; A. R. Nisha; C. Divya; S. G. Sangeetha; C. G. Umesh; R. C. Sundararajan; et al. (Theoretical and Applied Climatology, 2024)

Nanosilica from Averrhoa bilimbi juice pre-treated rice husk: Preparation and characterization - Midhun Dominic C D; Neenu K V; P.M. Sabura Begum; Rani Joseph; Derval dos Santos Rosa; Yongxin Duan; Aiswarya Balan; T.G. Ajithkumar; Mary Soumya; Ankita Shelke; Jyotishkumar Parameswaranpillai; Michael Badawi (Journal of Cleaner Production, 2023)